Social interaction attenuates the extent of secondary neuronal damage following closed head injury in mice - Doulames, Vanessa M.; Vilcans, Meghan; Lee, Sangmook; Shea, Thomas B. (Frontiers in Behavioral Neuroscience, 2015)
Recovery following Traumatic Brain Injury (TBI) can vary tremendously among individuals. Lifestyle following injury, including differential social interactions, may modulate the extent of secondary injury following TBI. To examine this possibility under controlled conditions, closed head injury (CHI) was induced in C57Bl6 mice using a standardized weight drop device after which mice were either housed in isolation or with their original cagemates (“socially-housed”) for 4 weeks. CHI transiently impaired novel object recognition (NOR) in both isolated and social mice, confirming physical and functional injury. By contrast, Y maze navigation was impaired in isolated but not social mice at 1–4 weeks post CHI. CHI increased excitotoxic signaling in hippocampal slices from all mice, which was transiently exacerbated by isolation at 2 weeks post CHI. CHI slightly increased reactive oxygen species and did not alter levels of amyloid beta (Abeta), total or phospho-tau, total or phosphorylated neurofilaments. CHI increased serum corticosterone in both groups, which was exacerbated by isolation. These findings support the hypothesis that socialization may attenuate secondary damage following TBI. In addition, a dominance hierarchy was noted among socially-housed mice, in which the most submissive mouse displayed indices of stress in the above analyses that were statistically identical to those observed for isolated mice. This latter finding underscores that the nature and extent of social interaction may need to vary among individuals to provide therapeutic benefit.